Molecular Orientations of Delayed Fluorescent Emitters in a Series of Carbazole-Based Host Materials - Sasabe, Hisahiro; Chikayasu, Yuki; Ohisa, Satoru; Arai, Hiroki; Ohsawa, Tatsuya; Komatsu, Ryutaro; Watanabe, Yuichiro; Yokoyama, Daisuke; Kido, Junji (Frontiers in Chemistry, 2020)
Molecular orientation is one of the most crucial factors to boost the efficiency of organic light-emitting devices. However, active control of molecular orientation of the emitter molecule by the host molecule is rarely realized so far, and the underlying mechanism is under discussion. Here, we systematically investigated the molecular orientations of thermally activated delayed fluorescence (TADF) emitters in a series of carbazole-based host materials.Enhanced horizontal orientation of the TADF emitters was achieved. The degree of enhancement observed was dependent on the host material used. Consequently, our results indicate that p-p stacking, CH/n (n = O, N) weak hydrogen bonds, and multiple CH/p contacts greatly induce horizontal orientation of the TADF emitters in addition to the molecular shape anisotropy. Finally, we fabricated TADF-based organic light-emitting devices with an external quantum efficiency (EQE) of 26% using an emission layer with horizontal orientation ratio (Q) of 79%, which is higher than that of an almost randomly oriented emission layer with Q of 62% (EQE = 22%).